Many Seconds into the Future : Ten Stories - Clayton, John Jacob (Book collections on Project MUSE., 2014)
"Moving stories of Jewish sensibility The stories in John J. Clayton's newest collection are luminous, expressing a struggle to see growth and meaning in life as much as possible. Nearly all focus on family, and the characters, most of them Jewish, grapple with questions of living, dying, loving, and worshipping. Clayton has published several novels, including Mitzvah Man (TTUP, 2011), but he is best known for his critically-acclaimed short fiction, which have been included in O. Henry Prize Stories, Best American Short Stories, and Pushcart Prize anthologies. His collection Radiance was a finalist for the National Jewish Book Award. The ten stories in Many Seconds into the Future were written after Clayton's collected stories were published in Wrestling with Angels in 2007. Many of these new stories originally were published in Commentary and some in literary magazines. Some are appearing for the first time. They are masterful stories of spiritual questing, emotional depth, and often great humor"--